The effects of 8 weeks of aerobic training on serum levels of chemerin and omentin in overweight women - abdolreza kazemi; Khatereh Naderi pour (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Obesity is one of the most important causes of mortality in developing countries. Omentin-1 and chemerin, as cytokines secreted by adipose tissue, are associated with obesity. Chemerin is considered a bridge between obesity and the exacerbation of diabetes type II. On the other hand, omentin-1 plays a role in regulating energy metabolism and body fat distribution in the body. The aim of the present study was to determine the effect of 8-week aerobic training on the serum levels of chemerin and omentin-1 in overweight women. Methods: This semi-experimental study was conducted on 21 overweight women with a pretest-posttest design and a control group. The study population was randomly divided into two groups of exercise (n=11) and control (n=10). The training program consisted of moderate aerobic training, including 30 min of running within 50-70% of maximum heart rate that was controlled with a Polar watch. This intervention was performed 3 sessions a week for 8 weeks. Blood samples were collected 48 h before the first session and 48 h after the last training session to measure the levels of serum omentin-1, chemerin, lipid profile, and insulin. Analysis of covariance was used to assess the differences between the groups. Results: The serum chemerin levels showed a significant reduction in the exercise group as compared to that in the control group (P=0.023). In addition, the serum levels of omentin-1 significantly increased in the exercise group, compared to that in the control group (P≤0.001). Conclusion: Aerobic exercises can improve the body composition and regulate the serum levels of insulin and glucose, thereby regulating the serum levels of chemerin and omentin-1 as adipokines. It seems that 8 weeks of aerobic exercise training accompanied by the elevation of omentin-1 level and reduction of chemerin level and factors related to obesity have an important role in the  improvement of cardiovascular health and metabolic disorders associated with obesity in overweight women.